Ansiedler (Settler) mit Hunden : [19--] - Lenz, Berthold, 1873-1960. (2001)
Black and white photograph of a man with a group of Eskimo dogs. The man is a settler (Kablunângajuit) in one of the Moravian missionary settlements. Black and white photograph of a man with a group of Eskimo dogs. The man is a settler (Kablunângajuit) in one of the Moravian missionary settlements.